Was Ishmael or Isaac taken for sacrifice? - A.S. Abraham (Johor Bahru, Johor : Afdal Handal Sdn. Bhd., 2003)
Judaism and Christianity believe it was Isaac who was taken for the sacrifice. Islam believes it was Ishmael. This is an intellectual analysis on genesis to pinpoint the truth about Abraham and his family. The findings are just like the sun shining over darkness of doubts and controversies.
Formerly known as'Secrets of Abraham's family in genesis'
Bibliography : page 118.
Keywords: Isaac (Biblical patriarch) -- Sacrifice; Ishmael (Biblical figure) -- In rabbinical literature; Abraham (Biblical patriarch) -- In the New Testament; Abraham family